Interleukin-13-induced MUC5AC Is Regulated by 15-Lipoxygenase 1 Pathway in Human Bronchial Epithelial Cells - Zhao, Jinming; Maskrey, Ben; Balzar, Silvana; Chibana, Kazuyuki; Mustovich, Anthony; Hu, Haizhen; Trudeau, John B; O'Donnell, Valerie; Wenzel, Sally E (American journal of respiratory and critical care medicine, 2009)
15-Lipoxygenase-1 (15LO1) and MUC5AC are highly expressed in asthmatic epithelial cells. IL-13 is known to induce 15LO1 and MUC5AC in human airway epithelial cells in vitro. Whether 15LO1 and/or its product 15-HETE modulate MUC5AC expression is unknown. To determine the expression of 15LO1 in freshly harvested epithelial cells from subjects with asthma and normal control subjects and to determine whether IL-13-induced 15LO1 expression and activation regulate MUC5AC expression in human bronchial epithelial cells in vitro. Human airway epithelial cells from subjects with asthma and normal subjects were evaluated ex vivo for 15LO1 and MUC5AC expression. The impact of 15LO1 on MUC5AC expression in vitro was analyzed by inhibiting 15LO1 through pharmacologic (PD146176) and siRNA approaches in human bronchial epithelial cells cultured under air-liquid interface. We analyzed 15 hydroxyeicosatetraenoic acid (15-HETE) by liquid chromatography/UV/mass spectrometry. MUC5AC and 15LO1 were analyzed by real-time RT-PCR, immunofluoresence, and Western blot. Epithelial 15LO1 expression increased with asthma severity (P < 0.0001). 15LO1 significantly correlated with MUC5AC ex vivo and in vitro. IL-13 increased 15LO1 expression and stimulated formation of two molecular species of 15-HETE esterified to phosphotidylethanolamine (15-HETE-PE). Inhibition of 15LO1 suppressed 15-HETE-PE and decreased MUC5AC expression in the presence of IL-13 stimulation. The addition of exogenous 15-HETE partially restored MUC5AC expression. Epithelial 15LO1 expression increases with increasing asthma severity. IL-13 induction of 15-HETE-PE enhances MUC5AC expression in human airway epithelial cells. High levels of 15LO1 activity could contribute to the increases of MUC5AC observed in asthma.